Determinasi Kinerja Karyawan dan Produktivitas Kerja: Analisis Profesionalisme dan Pelatihan (Literature Review Manajemen Sumber Daya Manusia) - Dori Mittra Candana; Hapzi Ali; Zefriyenni Zefriyenni (Dinasti Review, 2023)
Previous or related research is essential to a research or academic dissertation. Previous or related studies can help strengthen theories and phenomena of the relationships or effects between variables. This article explains how to determine employee performance and employee work productivity in carrying out their work. Targeting professionalism and training with the targeted object are employees at PT Semen Padang (PERSERO) Tbk. The purpose of writing this article is to make a hypothesis about the influence between variables that will be used in further research. The results of this library survey are as follows: 1) Professionalism influences work productivity; 2) Training has an effect on employee performance; 3) Work productivity affects employee performance; 4) Training has an effect on work productivity; and 5) Work productivity affects employee performance.